Remdesivir-induced severe hypoglycemia in an elderly man without diabetes: a case report - Yasunori Nagano; Hisae Aoki; Juri David; Naoko Iwahashi Kondo; Makimi Aizawa; Toshiyuki Sumita; Yuki Hamada; Yuki Yamamoto; Kaoru Yamada (Journal of Pharmaceutical Health Care and Sciences)
Abstract Background Remdesivir is recommended to treat hospitalized patients with coronavirus disease 2019 (COVID-19). Remdesivir is known to affect glucose metabolism in individuals with and without diabetes. However, little is known about the possibility of hypoglycemia associated with remdesivir. Our case is the first report demonstrating the development of severe hypoglycemia following remdesivir treatment in an elderly man without diabetes. Case presentation A 73-year-old man developed COVID-19 following surgery for sigmoid volvulus. The patient’s medical history included surgery for posterior correction of scoliosis, Chiari malformation type I, and syringomyelia. There was no history of diabetes mellitus. The patient was started on remdesivir (200 mg on day 1, followed by 100 mg intravenously daily until day 9). On day 7, following remdesivir administration, the patient developed severe hypoglycemia with a blood glucose (BG) level of 25 mg/dL. On day 8 and 9 he repeatedly developed severe hypoglycemia following administration of remdesivir. Considering the timing of administration, the patient’s hypoglycemia could have been caused by remdesivir. Therefore, his treatment with remdesivir was discontinued. After discontinuation, his BG levels normalized. The Naranjo algorithm, a tool for evaluating the causality of adverse drug reactions, classified the event as “Probable” (6 points). Conclusions Remdesivir may have caused hypoglycemia in this case. Health care professionals should be aware of its potential effects on glucose metabolism and the risk of hypoglycemia when treating patients with remdesivir.